Personal capabilities, prior knowledge and social factors towards entrepreneurial intentions among science and technology students / Mohd Kassim Sapenee - Sapenee, Mohd Kassim (2016)
The purpose of this research is to examine the dete1minants of entrepreneurial intention among science and technology students at public universities in Kota Samarahan, Sarawak. A total of 214 respondents in both public universities participated in the survey. The public university involved in this research are Universiti Teknologi MARA (UiTM) and Universiti Malaysia Sarawak (UNIMAS). Data obtained was analysed using Statistical Package for Social Science (SPSS) version 22. The result reveals that social factor was found to be significant with strong correlation and positive relationship with the entrepreneurial intention. Meanwhile, the relationship between prior knowledge was found to be significant with moderate correlation and positive relationship with entrepreneurial intention. The main contribution of this paper has provided empirical evidence about the relationship between personal capabilities, prior knowledge, and social factor on entrepreneurial intention. Moreover, it reveals what is the factor that influencing the most on the entrepreneurial intention among science and technology students specifically in Kota Samarahan area. Areas for future research are also discussed in this research.